2019
DOI: 10.1016/j.dib.2019.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on growth curves of Boer goats fitted by ten non-linear functions

Abstract: Data on the description of growth of female Boer goats from the Mexican national breeding flock are presented. Goat meat is highly appreciated for the preparation of traditional dishes of Mexican cuisine, and its demand is on the rise. Boer goats are of relatively recent arrival in Mexico and the size of the performance-recorded flock has been increasing steadily in the last ten years. Repeated measures of body weight at different ages from birth to adulthood of Boer goats are scarce. When available, such data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
4
7
0
Order By: Relevance
“…Hence, the IW and IA in Boer goat based on Gompertz model were 20 kg and 92 days respectively. Morever, Najari et al (2007) The IW and IA values in animals studied with Gompertz were lower than Logistic models and similar to Boer goat (Garcia-Muniz et al, 2019). In this study, the mature weight of Kacang bucks was about 15 kg and reached at about 14-16 months old.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Hence, the IW and IA in Boer goat based on Gompertz model were 20 kg and 92 days respectively. Morever, Najari et al (2007) The IW and IA values in animals studied with Gompertz were lower than Logistic models and similar to Boer goat (Garcia-Muniz et al, 2019). In this study, the mature weight of Kacang bucks was about 15 kg and reached at about 14-16 months old.…”
Section: Resultssupporting
confidence: 57%
“…Malhado et al (2009) obtained the IW values in Dorper × Morada Nova (DMN); Dorper × Rabo Largo (DRL) and Dorper × Santa Ines (DSI) sheeps based on Gompertz model were 11,96 kg; 10.50 kg and 11.03 kg respectively with IA around 58.50 days (DMN), 67.10 days (DRL) and 75.70 days (DSI). Thus, Garcia-Muniz et al (2019) reported IW and IA in Boer goat based on Logistic model were 24.8 kg and 115.1 days respectively. Hence, the IW and IA in Boer goat based on Gompertz model were 20 kg and 92 days respectively.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The same values of AIC and BIC were obtained for Weibull, Bridges and Janoscheck models in the current study. García-Muñiz et al [37] also reported the same values of AIC and BIC for these growth curves models in goat. In fact, all Weibull, Bridges, and Janoscheck models use the Weibull distribution; however, Bridges and Janoscheck models have an initial body weight parameter for describing the postnatal growth of individuals.…”
Section: Discussionmentioning
confidence: 55%
“…One effort to improve the genetic quality of Kacang goats was through crossing with Boer buck goat. Boer goat was a beef type with fast body growth, good meat quality, and parasitic tolerance (Chong et al, 2019;Elieser et al, 2012;García-Muñiz et al, 2019). Boer has weaning weights 23.4±9.7 kg at the age of 112 days (Menezes et al, 2016) and adult male 120-150 kg at the age of 2-3 years (Nurgiartiningsih et al, 2006).…”
Section: Introductionmentioning
confidence: 99%